The Oxford handbook of Roman law and society - Du Plessis, Paul J.; Ando, Clifford; Tuori, Kaius (Oxford University Press, 2016)
"The Oxford Handbook of Roman Law and Society surveys the landscape of contemporary research and charts principal directions of future inquiry. More than a history of doctrine or an account of jurisprudence, the Handbook brings to bear upon Roman legal study the full range of intellectual resources of contemporary legal history, from comparison to popular constitutionalism, from international private law to law and society, thereby setting itself apart from other volumes as a unique contribution to scholarship on its subject. The Handbook brings the study of Roman law into closer alignment and dialogue with historical, sociological, and anthropological research into law in other periods. It will therefore be of value not only to ancient historians and legal historians already focused on the ancient world, but to historians of all periods interested in law and its complex and multifaceted relationship to society"--Book jacket
Literaturangaben
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Rome -- Social conditions; Rome -- Social life and customs; Recht; Gesellschaft; Römisches Reich; Römisches Recht